Proyecto de acompañamiento psicológico a personas que experimentan la pérdida de un ser querido, usuarios de la Funeraria “Los Lirios” en la ciudad de Quito - Vallejo Verdezoto, Luis Fernando (2014)
The loss of a loved one psychologically hits the bereaved relatives; as a result of a loss, the subject goes through an emotional change. This is characterized by symptoms of anxiety, anger, guilt, denial and lack of control. Symptoms manifested by the pain of loss, and begin the arduous task of understanding, that the loved object is no longer in the subject's life. (Freud, 1914). versus that people do not know what to do, nor do they know how to deal with it, or know to come